Avaliação hemodinâmica, glicêmica e cognitiva da infusão contínua de clonidina como coadjuvante de técnica anestésica padronizada em cirurgia bariátrica - Oliveira, Lorena Antonia Sales de Vasconcelos (2011)
Morbid obesity is very frequent nowadays. The morbidly obese patient presents important anatomical and physiological changes, and comorbidities of great clinical significance, particularly cardiovascular, respiratory and metabolic demands of the physician anesthesiologist must be aware of these peculiarities, so you can make a safe approach, considering that the surgical procedures have been increasingly appearing in this group of individuals. The objective of this clinical, prospective and not randomized, was to evaluate the effects of administration of the α2-adrenergic agonist clonidine as an adjunct to drug standardized anesthetic technique for obesity surgery in 36 patients who belonged to the group of morbid obesity at the university hospital . Were divided into two groups: the first group of 25 patients received clonidine administered by continuous infusion at a dose of 2 mcg / kg ideal body weight, which started ten minutes before induction of anesthesia and then maintained at a dose from 0,4 to 0,7 mcg / kg / h of ideal weight, having been discontinued in the early closure of the aponeurosis and the second group of 11 patients did not receive the infusion of the agonist, however the rest of the anesthetic technique was equal. The main variables evaluated were systolic and diastolic blood pressure, heart rate, bispectral index (BIS), the expired concentration of sevoflurane, pain sensation, the mini-mental state examination (MMSE) and levels glucose. With regard to demographics, there was no difference between the two groups. With respect to hemodynamic parameters, an increase of systolic and diastolic blood pressure at the time of surgical incision in the control group (P <0.05). There was no difference in cognitive function. It was observed a better postoperative analgesia in the clonidine group (P <0.05). There was no significant difference in glycemic levels in the peri-operative when they examined the two groups, but when we examined only patients in the clonidine group, we observed that in nondiabetic patients, there was a significant increase in blood glucose during the intraoperative (P <0.05), however, not to exceed 200 mg / dl. There was greater intraoperative hemodynamic control with the use of clonidine. The clonidine group showed a more rapid awakening at surgery and also achieved better analgesia in the postoperative period. The use of the drug did not interfere with the recovery of cognitive function. At low doses, clonidine did not cause changes in glucose levels in the perioperative period, however, in diabetic patients in which the agonist was administered, there was a better glucose control, which was not demonstrated in nondiabetic patients. Patients in both groups showed no adverse effects.